4x = -36 x = -9
2x + 2x + 146 + 26 = 172 4x + 172 = 172 4x = 0 x = 0
It is an equation and the value of x is 4
-4x + 6 = 26 Subtract 6 from both sides: -4x = 20 Divide both sides by -4: x = 20/-4 Solve for x: x = -5
If x = 3, (4 x 3) + 14 = 26 and (6 x 3) + 8 = 26.
-20 = -4x +6 add 20 to both sides 0 = -4x +26 4x = 26 x = 26/4 = 6.5
If the equation is -4x + 2 = 26, then you can solve like so: -4x + 2 = 26 -4x = 26 - 2 = 24 4x = -24 x = -6 Check: -6 * -4 = 24, 24 + 2 = 26
4x = -36 x = -9
2x + 2x + 146 + 26 = 172 4x + 172 = 172 4x = 0 x = 0
It is an equation and the value of x is 4
16x
Lets simplify the above given equation : -8 plus 6(-x - 3) plus 4x simplified as : -8-6x -18 +4x =-2x -26 . =-2(x+13).
11x + 2 = 26 + 7x Subtract 7x from both sides: 4x + 2 = 26 Subtract 2 from both sides: 4x = 24 Divide both sides by 4: x = 6
-4x + 6 = 26 Subtract 6 from both sides: -4x = 20 Divide both sides by -4: x = 20/-4 Solve for x: x = -5
If x = 3, (4 x 3) + 14 = 26 and (6 x 3) + 8 = 26.
8x + 23 + 4x - 7x = 64; Find X To make this easier, add like terms: (8x + 4x - 7x) + 26 = 64 Use the order of operations: (12x - 7x) + 26 = 64 5x + 26 = 64 -26 -26 5x = 38 5 5 Finally: x = 7(3/5)
4x+1 -3 = 26 first, +1 and -3 = -2 Move the -2 to the other side of the = sign, and it becomes +2. +26 +(+2) = 28 Now we have 4x = 28 Divide both sides by 4 and you have 4x/4 = 28/4 Perform that division and the answer is x = 7